Experimental investigation of static properties of magnetorheological elastomer - Alias, Nor Fazlinda; Asan Gani, Abdul Muthalif; Arpan, Khairul A.M.; Nordin, Nor Hidayati Diana (Springer International Publishing AG, 2018)
Magnetorheological elastomer (MRE) is a type of smart material made of natural or synthetic rubber ﬁlled with micron-sized magnetic particles. Its shear modulus and elasticity can be controlled by applying an external magnetic ﬁeld. In this study, a mounting system model is used to obtain displacement transmissibility factor. In the experimental analysis, three different MRE samples are manufactured by varying the percentage of magnetic par- ticles. The experimental investigations are carried out to characterize the quasi-static properties of these MREs by attaching them with universal testing machine in com- pression and tensile mode. In both modes, different cur- rents and velocities are applied to the samples. From the experimental results, a proportional relationship has been observed among the resisting force from MREs and applied excitation current, displacement and velocity. In most cases, the force has increased with the increasing per- centage of magnetic particles in the sample. However, the highest force is obtained from the sample with 30% mag- netic particles, at 2 A current and velocity of 4 mm/min. The results observed in this research would be useful for vibration control in applications such as engine mounting system.